Assessment of the influence of the normalized vegetation index on the fire situation in the fire-hazardous period - Rybakov A.V.; Ivanov E.V.; Dmitriev A.V.; Borisov A.E. (Научно-технический вестник Брянского государственного университета)
The paper presents an analysis of the parameter obtained by remote sensing of the planet Earth, the normalized vegetation index (NDVI index). The results of assessing the impact of the index on the occurrence of fires in a certain area are presented. Using the example of statistical data for the Krasnoyarsk Territory, the index values for two periods of spring and summer were obtained, and the influence of NDVI values on the change in the probability of a forest fire was estimated. Static data on the index were selected from the «data lake» of the Ministry of Emergency Situations of Russia, data is collected from 2014 to the present, and data on thermal points from 2012. The consequences after wildfires will cause significant damage to forestry in Russia, and to the environment as a whole. Therefore, the allocation of previously known areas with a high probability of a natural fire will not only improve preventive measures for prevention, but will also make it possible to prevent most of the consequences. This article considers one of the parameters obtained by remote sensing of the Earth NDVI of its change before and after the event in question (natural fire).